Informal Enterprises in Kenya - World Bank (World Bank, Washington, DC, 2016)
This note draws from an emerging literature on firm informality as well as data collected on micro enterprises and informal firms as part of the World Bank’s enterprise survey initiative for Kenya. The purpose of the note is to assess the main constraints facing informal firms, identify patterns of productivity and firm dynamics, and better understand drivers for formalization. Section one provides an overview of key characteristics and main investment climate constraints facing informal firms. In section two, patterns of informal firm finance are explored, while in sections three and four, labor productivity and drivers of firm growth are analyzed. Section five examines incentives to remain informal and policies that can catalyze formalization. This is followed by a conclusion. Due to the sampling methodology used, all results pertain to the sample of surveyed firms; hence, due caution is necessary in extrapolating the results to the broader informal sector in Kenya. Nevertheless, the assessment of the surveyed firms could provide important information on identifying policies as well as firm-level support that could boost productivity and catalyze formalization. This could have important implications for economic growth and job creation in Kenya.